Investigating Post-Menopausal Characteristics and Perceptions of the Menopausal Transition - Shamsher, Saadia; Wahab, Shakeela; Fatima, Syeda Sitwat (Journal of Gandhara Medical and Dental Science, 2024)
OBJECTIVES This study aimed to investigate the knowledge and perceptions of menopause among post-menopausal women. METHODOLOGY A descriptive cross-sectional study was conducted at Hayatabad Medical Complex, Medical, and Teaching Institute Peshawar from March 2022 to March 2023. Participants meeting the inclusion criteria were assessed using a semi-structured proforma covering demographic variables, knowledge, and attitudes toward menopause. Delving into knowledge and perceptions of menopause, the questionnaire probed participants about their awareness of menopause upon cessation of menstrual periods, knowledge of the age of menopause, understanding of menopausal symptoms, whether they perceived menopause as a disease, medical condition, or a natural process, and their opinions on the treatment of menopausal symptoms. RESULTS In a survey assessing menopausal characteristics and perceptions, 81% of women experienced natural menopause and 19% underwent surgical menopause. 85% had prior knowledge of menopause, but only 45% knew its typical onset age. 56% held a positive perception of menopause. Hot flashes and mood swings were reported by 55% of women, while 48% experienced insomnia. CONCLUSION Many post-menopausal women are not aware of menopausal symptoms. Tailored health education and comprehensive support are necessary to address knowledge disparities and provide holistic care for women in this transition.